Process optimization for microcystin-LR degradation by Response Surface Methodology and mechanism analysis in gas–liquid hybrid discharge system. - Zhang, Yi; Wei, Hanyu; Xin, Qing; Wang, Mingang; Wang, Qi; Wang, Qiang; Cong, Yanqing (Journal of Environmental Management)
A gas–liquid hybrid discharge system was applied to microcystin-LR (MC-LR) degradation. MC-LR degradation was completed after 1 min under a pulsed high voltage of 16 kV, gas–liquid interface gap of 10 mm and oxygen flow rate of 160 L/h. The Box–Behnken Design was proposed in Response Surface Methodology to evaluate the influence of pulsed high voltage, electrode distance and oxygen flow rate on MC-LR removal efficiency. Multiple regression analysis, focused on multivariable factors, was employed and a reduced cubic model was developed. The ANOVA analysis shows that the model is significant and the model prediction on MC-LR removal was also validated with experimental data. The optimum conditions for the process are obtained at pulsed voltage of 16 kV, gas-liquid interface gap of 10 mm and oxygen flow rate of 120 L/h with ta removal efficiency of MC-LR of 96.6%. The addition of catalysts (TiO 2 or Fe 2+ ) in the gas–liquid hybrid discharge system was found to enhance the removal of MC-LR. The intermediates of MC-LR degradation were analyzed by liquid chromatography/mass spectrometry. The degradation pathway proposed envisaged the oxidation of hydroxyl radicals and ozone, and attack of high-energy electrons on the unsaturated double bonds of Adda and Mdha, with MC-LR finally decomposing into small molecular products.